2017
DOI: 10.1515/popore-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phenotypic plasticity of Pseudanabaena catenata from the Svalbard archipelago

Abstract: Abstract:A filamentous benthic cyanobacteria, strain USMAC16, was isolated from the High Arctic Svalbard archipelago, Norway, and a combination of morphological, ultrastructural and molecular characterisation (16S rRNA gene sequence) used to identify to species level. Cell dimensions, thylakoid arrangement and apical cell shape are consistent with the Pseudanabaena genus description. The molecular characterisation of P. catenata gave 100% similarity with Pseudanabaena catenata SAG 1464-1, originally reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Khan et al. (2017) reported that different strains of Pseudanabaena cultured under different illumination and temperature conditions exhibited varied widths (ESD) ranging from 1.31 to 3.24 µm. By virtue of the ESD of the microalgae cells, Rhodomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al. (2017) reported that different strains of Pseudanabaena cultured under different illumination and temperature conditions exhibited varied widths (ESD) ranging from 1.31 to 3.24 µm. By virtue of the ESD of the microalgae cells, Rhodomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Para Buch & Bittencourt-Oliveira (2010), esses organismos são formadores de florações, e capazes de produzir hepatoxinas, neurotoxinas e dermatotoxinas, portanto, com efeitos diversos ao organismo, que segundo Calijuri;Alves & Santos (2006) Pseudanabaena é um gênero bem distribuido no mundo e bem comum em água doce, possui várias espécies planctônicas, ticoplanctônicas, metafíticas ou perifíticas, em reservatórios de águas oligo, meso e até eutróficas (Franceschini et al, 2010). A espécie Pseudanabaena catenata é um organismo de ambiente com temperatura média, porém pode se adaptar a temperaturas acima de 15 ºC, e a presença de maior incidência de luz pode provocar um efeito substancial sobre suas características morfológicas (Khan et al, 2017).…”
Section: Discussionunclassified